Elusive counter-cyclicality and deliberate opportunism? Fiscal policy from plans to final outcomes - Pina, Álvaro M. (2022)
Drawing on the European Commission’s Autumn forecasts, I estimate fiscal reaction functions with four different information sets, ranging from budget plans to final outcomes. I also analyse deviations from plans during budget implementation. In a panel of 15 EU countries from 1987 to 2006, moving from plans to final data generally weakens the counter-cyclicality of budget balances and expenditures (though not of revenues), and reinforces electoral effects. Deviations from plans play a negligible role in the former finding, as they are often acyclical; but have a major role in the latter, as they display a clear opportunistic pattern.